أخلاقيات العمل الإداري و دورها في تعزيز أهداف ادارة علاقات الزبون : دراسة ميدانية في الشركة العامة لصناعة الأثاث المنزلي /نينوى - أضواء كمال حسين الجراح (PROSPECTIVE RESEARCHES, 2023)
This research aims at to determining the ethics of administrative work and their role in promoting the objectives of CRM. It is a field study at the General Company for the manufacture of furniture/ Nineveh province), where the required research methodology design scenario reflects the correlations and influence between the ethic of the administrative work and objectives of customer relationship management as well as the representation of a set of main and subsidiary hypotheses that reflect these relations depending on the determining of the research variables and testing the correlations and influences as the scheme of the research led and pointing out a set of conclusions and proposals.